2014
DOI: 10.18632/oncotarget.2452
|View full text |Cite
|
Sign up to set email alerts
|

miR-524-5p suppresses the growth of oncogenic BRAF melanoma by targeting BRAF and ERK2

Abstract: It has been well documented that miRNAs can modulate the effectiveness of cancer-associated signaling pathways. Mitogen-activated protein kinase (MAPK/ERK) signaling plays an essential role in the progression of many cancers, including melanoma and colon cancers. However, no single miRNA is reported to directly target multiple components of the MAPK/ERK pathway. We performed a miRNA PCR array screening with various MAPK/ERK signaling activities. The miRNA array data revealed that the expression of miR-524-5p w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 47 publications
7
50
0
2
Order By: Relevance
“…The present study demonstrated that the expression levels of miR-524-5p were downregulated in gastric cancer tissues and cell lines, suggesting that miR-524-5p functions as a tumor suppressor in human gastric cancer, which is consistent with previous studies (24).…”
Section: A D C Bsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study demonstrated that the expression levels of miR-524-5p were downregulated in gastric cancer tissues and cell lines, suggesting that miR-524-5p functions as a tumor suppressor in human gastric cancer, which is consistent with previous studies (24).…”
Section: A D C Bsupporting
confidence: 93%
“…Dysregulation of miR-524-5p is a frequent event in several types of cancer, including a reduction in the expression of miR-524-5p in melanoma (10) and glioma cells (9). The present study demonstrated that the expression levels of miR-524-5p were downregulated in gastric cancer tissues and cell lines, suggesting that miR-524-5p functions as a tumor suppressor in human gastric cancer, which is consistent with previous studies (24).…”
Section: A D C Bsupporting
confidence: 92%
See 1 more Smart Citation
“…A possible tumor suppressor role for miR-524-5p may be in line with findings of this study showing how circulating miR-524-5p levels were significantly lower in plasma of patients compared with healthy controls. Preclinical data demonstrating that miR-524-5p overexpression inhibited melanoma cell proliferation and migration in human melanoma cell lines 51 are likely to support this notion.…”
Section: Discussionmentioning
confidence: 87%
“…MiR-524-5p has been shown to suppress melanoma cell proliferation, migration, and tumor formation by targeting multiple downstream effectors in the Ras/Raf/ERK pathway, including both Braf and ERK2. Interestingly, activation of the Ras/Raf/ERK pathway by growth-factor stimulation or overexpression of the constitutively active mutant V600E Braf results in decreased expression of miR-524-5p, suggesting a feedback loop affecting this signal regulation [ 32 ]. Besides miR-524-5p, other miRNAs such as miR-7 have also been implicated in targeting Raf in glioblastoma and adrenocortical carcinoma to dampen the downstream Ras signal [ 33 , 34 ].…”
Section: The Ras/raf/mek/erk Signaling Pathwaymentioning
confidence: 99%